The First Photochromic Affinity Switch for the Human Cannabinoid Receptor 2. Issue 1 (5th February 2018) - Dolles, Dominik; Strasser, Andrea; Wittmann, Hans‐Joachim; Marinelli, Oliviero; Nabissi, Massimo; Pertwee, Roger G.; Decker, Michael
Abstract: The h CB2 R plays an important in the immune system and is centrally expressed in microglia. The h CB2 R activated by agonists hold great therapeutic potential, e.g., in neuroinflammation. It is currently not yet elucidated how pathophysiological processes are mediated by the h CB2 R. Here, photochromic affinity switches based on a drugable benzimidazole core through azologization and computational studies are developed. Structure‐activity relationships (SARs) lead to compounds with high selectivity over h CB1 R that can be reversibly switched to a higher affinity cis ‐form proved on the receptor level by radioligand binding studies and translating into an affinity change in a functional GTPγS assay. cAMP ELISA and the change in expression level of two genes regulated by CREB proves that the compounds act as partial agonists. Abstract : Switching affinity : A highly h CB2 R‐selective benzimidazole changes solely affinity, but not efficacy, upon irradiation by UV.